Detection and Quantification of Human Herpes Viruses Types-6 and Cytomegaly Viruses in Sperm Samples of Patients with Fertility Disorders - had, Mohammed S.; Almahbobi , Taghreed F.; Fakhrildin , Muhammad-Baqir M-R (PT. Antis International Publisher, 2024)
Background; Viral infections are common around the world and cause many health problems. Infertility in men is a widespread health problem that can affect lifestyle and psychological state. Aims of the study; Study of the effect of herpes virus type 6 and cytomegalovirus on infertility disorders in men. Methodology; A case control study was done for a 100 specimens collected from men. This study has been conducted in Al Sader Medical City / Infertility Center / Al-Najaf Al-Ashraf and privet Center Dr. Ali Al-Ibrahimi for Embryos and Infertility in najaf . During the period from 10/10/ 2023 to 10/4/2024. The current study consisted of a sample size of 100 males, which was subsequently separated into two groups. The control group comprised 40 fertile men, aged 25 to 45 years, who had experienced both primary and secondary fecundity for at least twelve months. The Patients Cases group, consisting of sixty infertile males aged between 22 and 46 years, was categorized into two subgroups based on the type of infertility. There were forty-six guys who were classified as main infertility. There were a total of fourteen men who experienced secondary infertility. Male participants who are reproductive age, normal seminal analysis which is healthy and have a child as a Control group (Fertile men). Name of patient, sample number, Age (years), Education, housing area, Type of work, height, weight, Smoking, chronic diseases, History of surgery, Primary infertility, Secondary infertility, Sperm count, Sperm motility and Sperm morphology. Detection of CMV in semen plasma by CMV ELISA kit and detection of HHV 6 in semen plasma by HHV 6 ELISA kit. Result; The results showed that there was no statistical significance in age between the two groups. They also showed that there was statistical significance in smoking, type of infertility, and duration of infertility. The results showed statistical significance in the results for herpes and cytomegalovirus. There is also no statistical significance regarding the number of cases of cytomegalovirus infection according to age. On the contrary, there was statistical significance regarding age in herpes. The results also indicated that there was statistical evidence in the sperm analysis between the two groups. Conclusions; The statistical evidence between the two groups in the number of infection cases for all groups or by age indicates the role of viral infections in causing infertility in men.